Violência, diversidade sociocultural e subjetividades: as discursividades em narrativas de educadores(as) - Rodrigues, Enildo da Paixão (2014)
This study aims at the analysis of the senses of the violence phenomenon produced in a public school in Joao Pessoa. To do so, we focused on the problems narrated by the institution educators that are generated as linguistic material, specifically produced for this investigation. So, this is the guiding issue adopted: up to which point the school professionals’ narratives exhibit the senses of school violence, their type models, causes and consequences? Therefore, we investigated the linguistic-discursive resources of the testimonies on the theme, chiefly those whose discursiveness points out to behavioral attitudes of violence, due to intolerance with identification features of cultural diversity encountered in this school unit. The research is inserted in the area of Applied Linguistics and adopts a conception of language as social practice (MOITA LOPES, 2006). The investigation profiles notions of the French Discourse Analysis (DA) on discourse, inter-discourse and foucaultian theorization about discursive formation and practice, subjectivity modes and regulation devices, normalization and conduction of individuals in social institutions. The analyzed discursiveness show that the violence produced in the school has its origin in diversified situations, mostly as prejudicial and discriminating effects related to cultural diversity. In this sense, we suggest the need to redimension the discursive and pedagogical practices produced and circulating in the scholar institution.